THE QUR'AN MEMORIZATION (TAHFIDZ) PROGRAM AS A FLAGSHIP INITIATIVE IN ENHANCING STUDENT - Zainuddin, Zainuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to respond to global demands for quality human resources. One strategy that has proven effective is through the superior tahfidz Al-Qur'an program implemented at the Siti Chodijah Islamic Elementary School. This research explores and analyzes management strategies that can empower the optimal potential of the program to improve student quality. A qualitative approach was used to examine the implementation of management strategies in various educational institutions that have succeeded in achieving excellence through the tahfidz Al-Qur'an program. The research results show that strategic management that focuses on the superior tahfidz Al-Qur'an program has a significant positive impact on improving the quality of education. This strategy includes careful planning, efficient resource management, empowering teaching staff, integrating technology, and establishing an inclusive Islamic learning culture. Implementation of this strategy consistently contributes to improving learning outcomes, strengthening Islamic values, and developing student character. These findings contribute to further understanding of strategic management in improving the quality of education through the tahfidz Al-Qur'an program. The practical implications of this research can be used as a reference for educational institutions in designing policies and implementing effective management strategies to achieve excellence in Islamic education. Thus, this research becomes a valuable guide for decision makers, administrators and educational practitioners who are interested in developing the quality of education through the implementation of superior Al-Qur'an tahfidz programs.